2003
DOI: 10.1038/sj.bjc.6601038
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for patients with hepatic metastases from breast cancer

Abstract: Median survival from liver metastases secondary to breast cancer is only a few months, with very rare 5-year survival. This study reviewed 145 patients with liver metastases from breast cancer to determine factors that may influence survival. Data were analysed using Kaplan -Meier survival curves, univariate and multivariate analysis. Median survival was 4.23 months (range 0.16 -51), with a 27.6% 1-year survival. Factors that significantly predicted a poor prognosis on univariate analysis included symptomatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
125
3
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(149 citation statements)
references
References 28 publications
16
125
3
5
Order By: Relevance
“…It is difficult to know whether this reflects differences in treatment, or the increased likelihood of dying from other conditions. We have seen a similar trend for worsening survival in our elderly patients with liver metastases, which seems in part explained by differences in treatment, with only 6.4% receiving chemotherapy compared to 56% of patients under 70 years (Wyld et al, 2002). Death from comorbid conditions has been put forward as an argument for the apparent poor survival in individuals over 70 years of age (Yanick et al, 2001).…”
Section: Discussionsupporting
confidence: 58%
“…It is difficult to know whether this reflects differences in treatment, or the increased likelihood of dying from other conditions. We have seen a similar trend for worsening survival in our elderly patients with liver metastases, which seems in part explained by differences in treatment, with only 6.4% receiving chemotherapy compared to 56% of patients under 70 years (Wyld et al, 2002). Death from comorbid conditions has been put forward as an argument for the apparent poor survival in individuals over 70 years of age (Yanick et al, 2001).…”
Section: Discussionsupporting
confidence: 58%
“…In this study, hepatic metastases from breast cancer had a median survival time of 16.0 months which is similar to the results quoted by Wyld et al (Zinser et al, 1987;Wyld et al, 2003) and better than the findings of other studies (Patanaphan et al, 1988;O'Reilly et al, 1990;Hoe et al, 1991). On multivariate analysis in this study, hepatic metastatic interval after initial diagnosis, treatment with surgery, and endocrine therapy, which for hepatic metastases, were the independent prognostic factors for hepatic metastases breast cancer.…”
Section: 5081 Clinical Characteristics and Survival Analysis Of Breasupporting
confidence: 80%
“…Those patients receiving endocrine therapy had a relatively good overall prognosis, with responders surviving for a median of 23.4 months. This was better than the outcome of previous study (Wyld et al, 2003). Interestingly, we found that endocrine therapy could improve the survival time of luminal subtype patients regardless of endocrine therapy to give patients at initial diagnosis of breast cancer whether or not.…”
Section: 5081 Clinical Characteristics and Survival Analysis Of Breacontrasting
confidence: 56%
“…The prognosis is poor in this area being the median survival of 1-20 months from the diagnosis of liver metastases [108,109,113,114]. Long survivals seem to be related to a positive endocrine treatment response, performed in the subgroup of patients with positive estrogen receptor pattern, with median survivals around 14 months compared to 4 months in the other cases [114].…”
Section: Liver Metastases From Breast Cancermentioning
confidence: 99%